Clinical Presentation of Heart Failure Patients Admitted in Colonel Maleque Medical College, Manikganj - Rahman, Md Toufiqur; Ahmed, Rashid; Alam, Rumi; Hossain, Mohammad Anowar; Hossain, Md Sarowar; Hossain, Mohammad Ashraf; Goni, Mohammad Nasimul; Rahman, Md Sajjadur; Hoque, Mohammad Faridul; Sarker, Manobendra (Bangladesh Journal of Medicine, 2023)
Background: Heart failure is a complex syndrome that arises from abnormalities in the structure and/or function of the heart, whether inherited or acquired. This increase in prevalence and incidence is due to a variety of factors, including the aging of the population, improved survival rates from other cardiovascular diseases, and changes in lifestyle and risk factors such as obesity and diabetes. Heart failure patients have various presentations and different etiologies. This study aimed to see the different clinical presentations of hospitalized heart failure patients. Methods: This study was done to see Clinical Presentation of Heart Failure Patients admitted in Colonel Maleque Medical College, Manikganj and Maikganj Sadar Hospital. Total 3650 patients were enrolled for this study during the period of April 2018 to March 2023. Results: Most of the patients (60%) were of 51-70 years age group. 70 % (2555) patients were male. 99 % patients presented with SOB, 95 % patients had basal creps, 70% had orthopnoea, 49% had Paroxysmal Nocturnal Dyspoea (PND), 40% had leg edema and 25% had raised JVP. Average heart rate was 84 beats/min, average systolic B.P. was 128 mm Hg and average diastolic B.P. was 76 mm Hg. 49% population had hypertension, 39% patients had diabetes and 28% had concomitant respiratory illness. Average EF was 37 %. Ischemic Cardiomyopathy was the commonest (40%) cause of heart failure, acute coronary syndrome was the second leading (30%) cause, valvular heart disease and hypertension is the third common cause. Conclusion: Most of the heart failure patients are elderly age group. Most of the patients presented with shortness of breath and bilateral basal creps. Most patients had co-morbid other illness that influences the natural course of heart failure patients. Most common causes are ischemic cardiomyopathy, a sequel of ischemic insult of the heart. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 219